On‐Demand Bacterial Reactivation by Restraining within a Triggerable Nanocoating. Issue 34 (19th July 2020) - Feng, Pingping; Cao, Zhenping; Wang, Xinyue; Li, Juanjuan; Liu, Jinyao
Abstract: Bacteria have been widely exploited as bioagents for applications in diagnosis and treatment, benefitting from their living characteristics including colonization, rapid proliferation, and facile genetic manipulation. As such, bacteria being tailored to perform precisely in the right place at the right time to avoid potential side effects would be of great importance but has proven to be difficult. Here, a strategy of on‐demand bacterial reactivation is described by individually restraining within a triggerable nanocoating. Upon reaching at a location of interest, nanocoatings can be triggered to dissolution in situ and subsequently decoat the bacteria which are able to recover their bioactivities as needed. It is demonstrated that gut microbiota coated with an enteric nanocoating can respond to gastrointestinal environments and reactivate in the intestine by a pH‐triggered decoating. In virtue of this unique, coated bacteria remain inactive following oral administration to exempt acidic insults, while revive to restore therapeutic effects after gastric emptying. Consequently, improved oral availability and treatment efficacy are achieved in two mouse models of intestinal infection. Bacteria restrained by a triggerable nanocoating represent a smart therapeutic that can take effect when necessary. On‐demand bacterial reactivation suggests a robust platform for the development of precision bacterial‐mediated bioagents. Abstract : Bacteria being tailored to perform therapeutic effects precisely in the right place at the right time to avoid potential side effects is important but has proven to be challenging. A strategy of on‐demand bacterial reactivation is described by restraining within a triggerable nanocoating. Upon reaching at a location of interest, the bacteria can be liberated to reactivate as needed.